Comparison of blind oro-tracheal intubation through LMA Blockbuster and LMA Protector – A prospective randomized study - Kiranpreet Kaur; Tavleen Kaur; Prashant Kumar; Mamta Bhardwaj; Svareen Kaur; Suresh K. Singhal; Sakshi Talwar; Paramjeet Sandhu (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: The present study was planned to compare two devices, namely LMA Blockbuster and LMA Protector, as a conduit for endotracheal intubation. The study aimed to compare the first-pass success rate of blind intubation, time taken for successful intubation, and ease of intubation through both devices. Material and Methods: This prospective randomized study was conducted on 100 patients of either sex aged 18–60 years, belonging to ASA physical status I–II, with 50 patients in each group (group B – LMA Blockbuster, and group P – LMA Protector). All the patients received general anesthesia. The primary objective was to compare the success rate, ease of blind tracheal intubation, time taken for intubation, and number of attempts. Secondary objectives included assessing the success of supraglottic device (SAD) placement, oropharyngeal seal pressure, and hemodynamic changes. Results: The insertion time of the SAD was 8.18 ± 3.66 and 10.94 ± 6.66 s for groups B and P, respectively. The SAD was placed on the first attempt in 96.0% of patients in group B and 88% of patients in group P. The total time taken for successful intubation was comparable between the groups (P = 0.239). The ETT was placed in the first attempt in 88% and 78% patients in group B and group P, respectively (P = 0.8). Conclusions: We conclude that LMA Blockbuster and LMA Protector are both comparable and good intubating devices in terms of ease and success rate of intubation. However, LMA Blockbuster outperforms LMA Protector in terms of ease of insertion of SADs.